Pengembangan Strategi Pembelajaran Tahfidz Pada Anak Usia Dini Di Tahfidz Kids Club ( TKC) Ar Raihan Sumber Sari Jember - Fajar Abdillah (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2024)
Tahfidz Kids Club ar-Raihan is also one of the tahfidz institutions that organizes tahfidz programs for early childhood. Ar Raihan has a tahfidz class for early childhood aged 2-3 years with lessons starting at 07.00-13.00. Of course it is not easy to package instruction with a relatively long time for young children who are still playing, get bored easily, depending on their parents. On that basis, this research wants to explore how to develop activities, methods, and learning media for Tahfidz in Early Childhood at Tahfidz Kids Club ar-Raihan Sumber Sari Jember. This research uses descriptive qualitative method. case study research design (case study) with a single case study type. The informant determination technique in this study used purposive sampling. Data collection techniques using observation, interviews and documentation. Data analysis using Miles and Huberman. The results of this study indicate that the development of tahfidz learning activities for early childhood at Tahfidz Kids Club ar Raihan Sumbersari Jember includes preliminaries by building motivation through independent habits in class from an early age, learning habits instead of playing, habits of listening to verses of the Koran, habits of memorizing , extrinsic reinforcement by giving extrinsic gifts in the form of stickers, food and drinks, listening to the verses of the Koran recited by sheikh Dr. Kamil al-Laboudy in the form of video through television media, Deposit verses that have been listened to before, provide feedback and reinforcement in the form of stickers or snacks, ending with the second joint murajaah. The development of the tahfidz learning method for early childhood at the Tahfidz Kids Club ar Raihan Sumbersari Jember is to make the tasmi' and takrir methods the main method, the al-targhib wa al-tarhib method as the supporting methods. The development of tahfidz learning media for early childhood at the Tahfidz Kids Club ar Raihan Sumbersari Jember is a flat screen television featuring Sheikh Dr. Kamil al-Laboudy and his attractively packaged son Tabarak are his main media. The video content files are limited to those who received the shahadah from Sheikh Dr. Kamil al-Laboudy.